Takaful protection for mental health illness from the perspective of Maqasid Shariah - Khairil Faizal Khairi; Mohamad Subini Abdul Samat; Nur Hidayah Laili; Hisham Sabri; Mohamad Yazis Ali Basah; Asmaddy Haris; Azrul Azlan Iskandar Mirza (Sciedu Press, 2024)
Indexed by Scopus/ERA